A Systematic Review of Cyberstalking Victimization and Offending Behaviors - Marcum, Catherine Davis (American journal of criminal justice, 2021)
A systematic review of literature investigating cyberstalking offending and victimization was conducted, considering multiple key words and phrases used to label the behavior: cyberstalking, cyber dating abuse, cybervictimization, Internet, interpersonal electronic surveillance, and victimization. The following electronic databases, with the indication of peer-reviewed journal articles as a requirement, were searched: Academic Search Complete, Criminal Justice Database (ProQuest), Google, JSTOR and PsychInfo. After sorting through the studies using the inclusion and exclusion criteria, 31 studies remained for review. Correlates of the behaviors were discussed for each categorization, with main themes including negative characteristics of relationship behaviors, and social media and online use as main predictors of victimization and offending. There is a strong need for further research utilizing older age groups and individuals who are married, as well as a need for longitudinal research.